ANALISIS KEMAMPUAN MEMBACA TEKS ARAB GUNDUL BAGI SANTRI PONDOK PESANTREN AL MIMBAR SAMBONG DUKUH JOMBANG - Nurul Hidayah; Anisa Mulyani (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
Abstract The ability to read is a basic abilitythat must be possesed by everyone, especially those related to bald Arabic text or what is called the yellow book. It takes a very deep tenacity to learn it, starting from memorizing vocabulary and understanding the science of nahwu and shorof. Therefore, the yellow book became the main source of a boarding school. To find out these problems, researchers conducted a study aims to determine the ability of the students of the Al Mimbar Islamic Boarding School Jombang.The method used by the researcher in this research is descriptive qualitative by using four techniques in collecting data, namely: Observation, Interview, Test and Documentation. The results of the study illustrate that: 1) The students of the Al Mimbar Islamic Boarding School are categorize as being able to fluently read harakat while they are less ables to answer grammatical material. 2) The method used in learning Arabic text at the Al Mimbar Islamic Boarding School is only Bandongan method. 3) The factors that hinder students’ ability to read the yellow book are the learning of bare Arabic text and Arabic rules in particular and the low interest of students in learning the Arabic rules. Keywords: Reading, Bald Arabic text, Santri